Volatile and Non-Volatile Single Electron Memory - A. Touati; A. Kalboussi (Журнал нано- та електронної фізики)
Multi Tunnel Junctions (MTJs) have attracted much attention recently in the ﬁelds of Single-Electron Devices (SED) in particular Single-Electron Memory (SEM). In this paper, we have design and study a nano-device structure using a two dimensional array MTJs for Volatile and Non-Volatile-SEM, in order to analyze the impact of physical parameters on the performances. We investigate the single-electron circuit characteristics in our devices qualitatively, using single-electron Monte Carlo simulator SIMON.